Modelling and implementation of an intelligent stowage simulator for container ships. (7th May 2020) - Wang, Qingwu; Zhao, Jian; Ma, Lin
To solve the problems that conventional loading master for container ship merely provides the stability, strength, floating condition, etc. a comprehensive intelligent simulator was worked out, which can also obtain the amount of restowage containers, verify segregation scheme for dangerous containers, etc. BLOCK algorithm is proposed for the first time for restowage problems with respect to the containers on deck jam that in hold and all in hold or on deck. In the case of all in hold or on deck, independent stowage and mix stowage are studied in some detail. A fast and effective algorithm is also put forward to perform the segregation verifying. At last, the above proposed algorithms are verified by the loading condition from the loading manual.